Preparation and characterization of Chromium-Doped Ni-Cu-Zn Nano Ferrites - Bajarang Laxman Shinde; Laxman Appa Dhale; Venkat S. Suryavanshi; Kishan Shankarrao Lohar (Acta Chimica Slovenica, 2017)
Chromium doped Ni-Cu-Zn nano ferrites with chemical formula Ni0.2Cu0.2Zn0.6Fe2-xCrxO4 (x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0) were prepared by using sol-gel auto combustion method. The prepared precursors of Chromium substituted Ni-Cu-Zn ferrites were sintered at 500 0C for 4h. Compositional stoichiometry were confirmed from EDAX patterns. The XRD data revealed that the all samples possess a single phase cubic spinel structure. The Lattice constant, X-ray density, hopping lengths and crystallite size determined from XRD data decreases with increase in Cr3+ concentration. The IR spectra show two major absorption bands, high frequency band ν1 ≈ 600 cm-1 and low frequency band ν2 ≈ 450 cm-1 attributed to the stretching vibration of tetrahedral and octahedral sites respectively. The surface morphology of the prepared samples was studied by Scanning Electron Microscopy and Transmission Electron Morphology.